Pengembangan Aplikasi Analisis Rantai Nilai Produk KainGray di Perusahaan Tekstil (Studi Kasus: PT XYZ) - Kristina, Sonna; Gunawan, Julia (Jurnal Telematika, 2017)
The main objective of this study is to identify every primary and supporting activity of the value chain of gray cloth products in textile companies and to know the value addition of gray cloth within the company. The value chain mapping steps use the Porter value chain with some adjustments in several stages. The steps are primary and supporting activities identification, value chain mapping, added value calculation, SWOT analysis, key activity determination based on price sensitivity analysis, and key activity analysis based on SWOT analysis and price sensitivity analysis. The result of the study shows that the value chain of gray cloth products in PT XYZ is  running well because every activities, both primary and supporting, are interconnected, thus affecting the success of the company. The percentage of added value of gray cloth is relatively high which allows textile companies to continue growing and competing on a global scale. There are several internal and external factors that may become strengths and weaknesses, therefore in this study  those factors should be considered in order for the textile companies to be able to grow and compete. Key activities based on price sensitivity analysis is procurement activities because the most influence the price of polyester yarns. The result of key activity analysis based on SWOT analysis and sensitivity analysis stated that the price of polyester yarn  has the greatest price sensitivity and is influenced by procurement activity, procurement activity based on SWOT analysis is one of the activities that become the strength of  the value chain of gray cloth product. The results of this analysis will be applied in the application of information systems in textile companies. Therefore procurement activity such as the selection of raw material suppliers need to be considered based on price so that  textile companies can continue to grow and can compete globally..Tujuan utama dari penelitian ini adalah mengidentifikasi setiap aktivitas primer dan aktivitas pendukung rantai nilai produk kain gray di perusahaan tekstil serta mengetahui pertambahan nilai kain gray di dalam perusahaan. Langkah-langkah pemetaan rantai nilai menggunakan rantai nilai Porter dengan beberapa penyesuaian dalam beberapa tahapan. Langkah awal yang dilakukan adalah identifikasi aktivitas primer dan pendukung, pemetaan rantai nilai, perhitungan nilai tambah, analisis SWOT, penentuan aktivitas kunci berdasarkan analisis sensitivitas harga serta analisis aktivitas kunci berdasarkan SWOT dan analisis sensitivitas. Hasil penelitian didapati bahwa rantai nilai produk kain gray di PT XYZ berjalan dengan baik karena setiap aktivitas baik aktivitas primer dan aktivitas pendukung saling berhubungan sehingga mempengaruhi keberhasilan suatu perusahan. Persentase nilai tambah kain gray tergolong tinggi sebesar  55,71% sehingga perusahaan tekstil dapat terus tumbuh dan bersaing secara global.  Terdapat beberapa faktor internal dan eksternal yang menjadi kekuatan dan kelemahan sehingga perlu diperhatikan pada penelitian ini agar perusahaan tekstil dapat terus tumbuh dan bersaing. Aktivitas kunci berdasarkan analisis sensitivitas harga adalah aktivitas procurement karena paling mempengaruhi harga benang polyester. Hasil dari analisis aktivitas kunci berdasarkan SWOT dan analisis sensitivitas menyebutkan bahwa harga benang polyester memiliki sensitivitas harga yang paling besar dan dipengaruhi oleh aktivitas procurement, aktivitas procurement berdasarkan analisis SWOT merupakan salah satu aktivitas yang menjadi kekuatan rantai nilai produk kain gray. Hasil analisis ini akan diterapkan dalam aplikasi sistem informasi di perusahaan tekstil. Maka dari itu aktivitas procurement seperti pemilihan supplier bahan baku perlu diperhatikan berdasarkan harga agar perusahaan tekstil dapat terus tumbuh dan dapat bersaing secara global.